Kompetensi Profesional Pendidik Menurut Al-Ghazali - Ismatul Maula (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2020)
Competence is the initial basis for a teacher to carry out his duties in teaching, but today many teachers do not understand the importance of a competency. Many of those who teach are limited to fulfilling their obligations without considering competency aspects which are the basic foundation in learning. al-Ghazali as a figure in Islamic education contributed a lot of thought in the world of education, among which he was concerned with the components of teachers and students. In thinking about the teacher he discussed in the book of IhyÄ â€˜UlÅ«m al-AddÄ«n Volume 1 Chapter al-â€˜Ilm. Al-Ghazali explained how educator professional competence must be possessed before carrying out teaching assignments. The problem of this research is